[Rezension von: Goren, Ḥayim, 1946-, "The loss of a minute, is just so much loss of life" : Edward Robinson and Eli Smith in the Holy Land] - Popa, Cătălin-Ştefan ca. 20./21. Jh. (Review of ecumenical studies, 2022)
Sciendo provides publishing services and solutions to academic and professional organizations and individual authors. We publish journals, books, conference proceedings and a variety of other publications.